A baseline estimate of regional agricultural water demand from GEO-LEO satellite observations. Issue 12 (4th August 2022) - Choudhury, Indrani; Bhattacharya, Bimal Kumar
Abstract: Agricultural water demand (AWD) and irrigation water demand (IWD) were assessed (2009–2018) over India using geostationary and polar orbiting satellites. A novel concept of satellite based composite crop-coefficient was introduced to address bulk AWD from mixed agricultural landscape. Significant spatio-temporal variation of AWD was observed over India. The decadal mean of annual AWD was found to be 1521 km 3 contributing around 52% (789 km 3 ) and 48% (732 km 3 ) in kharif and rabi seasons, respectively. The decadal average IWD over India was found to be 360 km 3 . At annual scale, around 75% of AWD was found fulfilled by effective rainfall and the rest 25% is the IWD. The decadal trend of AWD and IWD showed significant increasing trend over Indian region. The study provides a baseline reference for regional agricultural water management policy over diverse agro-climatic regions of India with an opportunity to optimize AWD and IWD at different locations.